Forecasting Geotechnical Characteristics of Diverse Soils through CIPW Norm Analysis (International Journal of Food and Nutritional Sciences, 2023)
The fundamental physical attributes of a rock mass are dictated by the nature of the rock(s). Likewise, thefoundational properties of a soil mass are intricately linked to the characteristics of its parent rock(s). Soilcomposition comprises minerals resulting from the weathering of rocks prevalent across the Earth's surface. Todiscern the impact of mineral composition on geotechnical properties, civil engineers can predict soil propertiesthrough normative mineral analysis, which delineates the mineral composition percentage.